Temporary Intraoperative Handoff Report Among Nurse Anesthetists: Utilization of Standardized Handoff Tools and Barriers to Implementation. - Allen, Rachael; Nemec, Candice; O'Guin, Crystal; Wright, Suzanne; Dalley, Carrie Bowman (AANA Journal, 2023)
The demanding nature of the intraoperative period presents several distractions to anesthesia providers that can hinder effective communication. Implementation of intraoperative and postoperative standardized handoff protocols have improved provider communication; however, these protocols remain underutilized. While temporary anesthesia handoffs arise more frequently than permanent handoffs, limited data exist on how the specific transfer of care processes transpire. The purpose of this study was to explore the usage of standardized handoff tools among certified registered nurse anesthetists, as well as the barriers to implementation during temporary intraoperative handoff. Data from this exploratory mixed-methods study were collected using a 16-question voluntary electronic survey. Most participants (81.2%) reported that they do not use a standardized handoff tool during temporary handoff, but over half (57.1%) believed such tools should be used. Study participants who used a standardized handoff tool were significantly less likely to rank "increases the time spent giving a handoff" as an important barrier (48.6%) compared with those who did not use a tool (71.9%), (X²(1) = 7.39, P = .007, V = .19). Failure to make standardized handoffs a facility standard of care and lack of reception by receiving anesthesia providers were also ranked as major barriers to implementation.